STOP— a training intervention to optimise treatment for smoking cessation in community pharmacies: cluster randomised controlled trial - Sandra Jumbe; Vichithranie W. Madurasinghe; Wai Yee James; Colin Houlihan; Samantha L. Jumbe; Tammy Yau; Florian Tomini; Sandra Eldridge; Borislava Mihaylova; Liz Steed; Ratna Sohanpal; Darush Attar; et al. (BMC Medicine, 2022)
Abstract Background Community pharmacies serve people with high levels of tobacco-related illness, but throughput in NHS Stop Smoking Services in pharmacies remains relatively low. We investigated the effectiveness of a complex intervention to increase service uptake and retention. Methods We randomised 60 pharmacies in England and Wales to the STOP intervention or usual practice in a pragmatic, parallel-group, controlled trial over 11 months. Smokers were blind to the allocation. The intervention was theory-based consultation skills training for pharmacy staff with environmental prompts (badges, calendars and behavioural cues). The primary outcome was the number of smokers attending an initial consultation and setting a quit date. Results The intervention made no significant difference in setting a quit date, retention or quit rate. A total of 631 adult smokers (service users) enrolled and set a quit date in intervention pharmacies compared to 641 in usual practice pharmacies, a rate ratio of 0.75 (95% CI 0.46 to 1.23) adjusted for site and number of prescriptions. A total of 432 (68%) service users were retained at 4 weeks in intervention and 500 (78%) in usual practice pharmacies (odds ratio 0.80, 0.41 to 1.55). A total of 265 (42%) service users quit smoking at 4 weeks in intervention and 276 (43%) in usual practice pharmacies (0.96, 0.65 to 1.43). The pharmacy staff were positive about the intervention with 90% (56/62) stating that it had improved their skills. Sixty-eight per cent would strongly recommend the training to others although there was no difference in self-efficacy for service delivery between arms. Seventy of 131 (53%) service users did not complete the 6-month follow-up assessment. However, 55/61 (90%) service users who completed follow-up were satisfied or very satisfied with the service. All usual practice arm service users (n = 33) and all but one in the intervention arm (n = 27) would recommend the service to smokers. Conclusions We found high levels of retention and acceptable quit rates in the NHS pharmacy stop smoking service. Despite pharmacy staff providing positive feedback on the STOP intervention, it made no difference to service throughput. Thus, other factors may currently limit service capacity to help smokers to quit. Trial registration ISRCTN, ISRCTN16351033 . Retrospectively registered.